The magnitude of short interpregnancy intervals and associated factors among women who delivered in North Wollo Zone public hospitals, northeastern Ethiopia, 2023: A facility-based cross-sectional study - Mulugeta Wodaje Arage; Samrawit Shimels; Abebe Tarekegn Kassaw; Gizachew Yilak (SAGE Publishing, 2024)
Background: Maternal and child mortality rates remain a serious public health challenge in Ethiopia. Short interpregnancy intervals are known to negatively impact perinatal and child health; therefore, improving this practice is a key strategy to reduce mortality and adverse outcomes. Objective: This study aimed to evaluate the extent of short intervals between pregnancies and the factors associated with them among women who gave birth at public hospitals in the North Wollo Zone of northeastern Ethiopia in 2023. Design: A facility-based cross-sectional study was conducted in the North Wollo Zone of northeastern Ethiopia in 2023. Methods: This study was conducted on mothers who delivered at public hospitals in the North Wollo Zone of northeastern Ethiopia. The study participants were selected using a systematic random sampling technique between February 1, 2023, and April 1, 2023. Data were collected through an interviewer-administered questionnaire using the Kobo Collect tool and analyzed using SPSS version 27.0. Bivariable and multivariable analyses were performed to determine the relationship between the outcome and predictor variables. A p value of less than 0.05 was considered significant in the multivariable analysis. Results: The study found that 51.5% of participants had short interpregnancy intervals. Several independent factors were associated with a short birth interval, including the status of the last pregnancy (adjusted odds ratio (AOR): 9.51; 95% CI: 3.932-23.0028), educational status of the woman (AOR: 4.545; 95% CI: 1.208-17.108), and use of modern contraceptives in previous pregnancies (AOR: 6.460, 95% CI: 3.882-23.008). Conclusion: Despite the efforts made through public health interventions in Ethiopia, the prevalence of short interpregnancy intervals in this study was high. Therefore, increasing the utilization of modern contraceptives and promoting health education at both health facilities and community levels could contribute to addressing this issue.